2023
DOI: 10.1101/2023.08.23.554532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The floral development of the allotetraploidCoffea arabicaL. correlates with a small RNA dynamic reprogramming

Thales Henrique Cherubino Ribeiro,
Patricia Baldrich,
Raphael Ricon de Oliveira
et al.

Abstract: Non-coding and coding RNAs are key regulators of plant growth, development, and stress responses. To investigate the types of transcripts accumulated during the vegetative to reproductive transition and floral development in the Coffea arabica L., we sequenced small RNA libraries from eight developmental stages, up to anthesis. We combined this data with messenger RNA and PARE sequencing of two important development stages that marks the transition of an apparent latent to a rapid growth stage. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Details of the small RNA libraries of C. arabica anthers in pre-meiosis, meiosis, and post-meiosis, including the numbers of Sequence Read Archive databases (SRAs), are available in Table S1. The PARE libraries for pre-meiotic, meiotic, and post-meiotic samples (Ribeiro et al, 2023) were used to identify miRNAs that trigger phasiRNAs production.…”
Section: Small Rna Libraries Construction (Illumina Sequencing)mentioning
confidence: 99%
“…Details of the small RNA libraries of C. arabica anthers in pre-meiosis, meiosis, and post-meiosis, including the numbers of Sequence Read Archive databases (SRAs), are available in Table S1. The PARE libraries for pre-meiotic, meiotic, and post-meiotic samples (Ribeiro et al, 2023) were used to identify miRNAs that trigger phasiRNAs production.…”
Section: Small Rna Libraries Construction (Illumina Sequencing)mentioning
confidence: 99%
“…In the genus Coffea, several families of conserved and new microRNAs have been identified [42,43,45,[107][108][109][110][111][112] in addition to the main proteins in the biosynthesis of sRNAs, such as DICER and Argonaute [44,113]. More recently, several types of non-coding RNAs were identified in C. canephora, in addition to miRNAs and their targets [114], and in C. arabica during floral development [46]. Hernández-Castellano et al [115] identified some families of miRNAs in embryogenic callus; the data suggest a differential and cooperative role for miR535, miR164, miR2119, and miR157a during the initial stages of somatic embryogenesis in C. canephora, supporting their regulatory role in cellular totipotency of plants, which can bring benefits to genetic improvement programs.…”
Section: The Srna Characteristics and Their Roles In Plant Stress Med...mentioning
confidence: 99%
“…However, despite some miRNAs in common, the list of miRNAs with altered expression varies with the degree of stress and between species. Although sRNAs in coffee plants have already been addressed in some studies, such as the identification of miRNAs and their biogenesis pathways [42][43][44][45], miRNAs in floral development [46] and reproductive development [47], there is still a gap relating the role of sRNAs in temperature control in these species. Therefore, considering the peculiar aspect of C. arabica origin related to the narrow diversity and the need for more adapted genotypes in the face of climate changes, this review contributes to the understanding of the roles of sRNAs in coffee plants and discusses perspectives on its use as tools for crop breeding.…”
Section: Introductionmentioning
confidence: 99%